Pathophysiological changes at single and multiple introduction of Ciprofloxacin solution under experimental conditions - A. G. Yushkov; M. M. Rasulov; P. A. Storozhenko; G. G. Yushkov; N. A. Shulgina; A. A. Gushchina (Acta Biomedica Scientifica, 2013)
The article presents the results of experimental biological modelling of single and subacute introduction of Ciprofloxacin to the rabbits. State of an organism of animals was estimated by biochemical, hematological, hemostatic and morphologic indices. Introduction of preparation samples was intravenous, according to the Instruction of medical use. Main result of the experiments is determination of toxic effects that are typical for fluorinequinolone and developed on the background of multiple introduction of preparation in the doses higher than therapeutic.